Normalization of host intestinal mucus layers requires long-term microbial colonization - Johansson, Malin E V (Cell Host Microbe, 2015)
The intestinal mucus layer provides a barrier limiting bacterial contact with the underlying epithelium. Mucus structure is shaped by intestinal location and the microbiota. To understand how commensals modulate gut mucus, we examined mucus properties under germ-free (GF) conditions and during microbial colonization. Although the colon mucus structure of GF mice was similar to conventionally raised (Convr) mice, the GF inner mucus layer was penetrable to bacteria-sized beads. During colonization, in which GF mice were gavaged with Convr microbiota, the small intestine mucus required five weeks to be normally detached and colonic inner mucus six weeks to become impenetrable. The composition of the small intestinal microbiota during colonization was similar to Convr donors until three weeks when Bacteroides increased, Firmicutes decreased, and segmented filamentous bacteria became undetectable. These findings highlight the dynamics of mucus layer development and indicate that studies of mature microbe-mucus interactions should be conducted weeks after colonization.